Instruments used in the assessment of expectation toward a spine surgery: an integrative review - Eliane Nepomuceno; Renata Cristina de Campos Pereira Silveira; Carina Aparecida Marosti Dessotte; Rejane Kiyomi Furuya; Eliana De Cássia Arantes; Débora Cristine Prévide Teixeira da Cunha; Rosana Aparecida Spadoti Dantas
Abstract OBJECTIVE To identify and describe the instruments used to assess patients' expectations toward spine surgery. METHOD An integrative review was carried out in the databases PubMed, CINAHL, LILACS and PsycINFO. RESULTS A total of 4,402 publications were identified, of which 25 met the selection criteria. Of the studies selected, only three used tools that had confirmed validity and reliability to be applied; in five studies, clinical scores were used, and were modified for the assessment of patients' expectations, and in 17 studies the researchers developed scales without an adequate description of the method used for their development and validation. CONCLUSION The assessment of patients' expectations has been methodologically conducted in different ways. Until the completion of this integrative review, only two valid and reliable instruments had been used in three of the selected studies.